Cost savings analysis of prescription assistance programs at a student-run free clinic. Issue 3 (4th May 2022) - Chow, Nathan; Snitman, Annie; Rafael, John; Bui, Stephanie; Bennett, Kelly; Prabhu, Fiona
Abstract: The Free Clinic at Lubbock Impact (TFC) is a student-run, volunteer free clinic affiliated with Texas Tech University Health Sciences Center in Lubbock, Texas, that provides free weekly health services to the local uninsured patient population. The clinic also helps patients enroll in prescription assistance programs (PAPs) from pharmaceutical companies, which supply eligible patients with certain medications at little or no cost. This study presents a cost savings analysis of TFC patients enrolled in PAPs from February 2019 through February 2020. Cost savings were calculated by matching medication doses and units with the cost per unit for each brand-name medication listed on GoodRx.com at Walgreens pharmacies located in TFC's zip code, 79410. Sixty-one patients received 23 different medications with a total cost savings value of 222, 563. Medications were sorted into diabetic, respiratory, and miscellaneous disease categories, for which cost savings totaled 114, 110, 60, 219, and 48, 234, respectively. This study highlights the value of utilizing PAPs at a free clinic to address the barrier of medication cost for uninsured patients in Lubbock, Texas, and surrounding areas.